The Essence of Barokah-Oriented Islamic Education in the Perspective of Ta'limul Muta'allim by Syekh Az-Zarnuji - Maysaroh; Ahmad Muzakki; Mohammad Solihin (Yayasan Azhar Amanaa Yogyakarta, 2026)
Contemporary Islamic education faces the challenges of pragmatism, moral crisis, and information disruption that threaten the essence of the barokah (blessedness) of knowledge. This study aims to analyze the nature of barokah-oriented Islamic education according to Syekh Burhanuddin Az-Zarnuji in the book Ta'limul Muta'allim Thariq at-Ta'allum, to identify the pedagogical principles that constitute the barokah of knowledge, and to examine their relevance to Islamic education in Indonesia. The method employed is qualitative content analysis with a hermeneutical approach to classical Islamic texts. The primary source is the Ta'limul Muta'allim in its original Arabic manuscript and authoritative translations, supplemented by secondary sources including classical and contemporary Islamic educational literature. The results show that Az-Zarnuji constructs a barokah-based educational framework through four main pillars: (1) sincerity of intention (lillahi ta'ala) as an ontological foundation; (2) ta'zhim al-ustadz as an epistemological condition; (3) adab toward knowledge as an axiological dimension; and (4) the holistic ta'allum method as pedagogical operationalization. These four pillars form an educational system that transcends cognitive transmission toward character and spiritual transformation. Its relevance in the modern Indonesian context lies in the capacity of this concept to serve as an antithesis to educational pragmatism and to offer a holistic educational model that integrates cognitive, affective, spiritual, and social dimensions.